The Conformation of the Mannopyranosyl Phosphate Repeating Unit of the Capsular Polysaccharide of Neisseria meningitidis Serogroup A and Its Carba‐Mimetic. Issue 33 (17th August 2018) - Calloni, Ilaria; Unione, Luca; Jiménez‐Osés, Gonzalo; Corzana, Francisco; Del Bino, Linda; Corrado, Alessio; Pitirollo, Olimpia; Colombo, Cinzia; Lay, Luigi; Adamo, Roberto; Jiménez‐Barbero, Jesús
Abstract : Neisseria meningitidis serogroup A (MenA) is an aerobic diplococcal Gram‐negative bacterium responsible for epidemic meningitis disease. Its capsular polysaccharide (CPS) has been identified as the primary virulence factor of MenA. This polysaccharide suffers from chemical lability in water. Thus, the design and synthesis of novel and hydrolytically stable structural analogues of MenA CPS may provide additional tools for the development of therapies against this disease. In this context, the structural features of the natural phosphorylated monomer have been analyzed and compared to those of its carba‐analogue, where the endocyclic oxygen has been replaced by a methylene moiety. The lowest energy geometries of the different molecules have been calculated using a combination of quantum mechanical techniques and molecular dynamics simulations. The predicted results have been compared and validated using NMR experiments. The results indicate that the more stable designed glycomimetics may adopt the conformation adopted by the natural monomer, although they display a wider flexibility around the torsional degrees of freedom. Abstract : The capsular polysaccharide of Neisseria meningitidis A is the major factor of virulence of these bacteria and suffers from poor stability in water. Ab initio techniques were used to identify more stable mimics, and the behavior of the natural Men A monosaccharide in solution was compared to that of a carbasugar analogue by MD simulation and NMR spectroscopy.